Speech of Mr. Hubbard, of New Hampshire, In Senate, March 7, 1836. - Hubbard, Henry (My University, 1836)
The memorial of the Society of Friends upon the subject of the abolition of Slavery in the District of Columbia and the question as to the proper mode of disposing of it, being before the Senate -- Mr. Hubbard submitted the following remarks: 1836.
Keywords: Abolitionist; Slavery; District of Columbia